1993
DOI: 10.1021/jf00025a030
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of triallate in Sprague-Dawley rats. 3. In vitro metabolic pathways

Abstract: Rat liver enzyme preparations were used to investigate the mechanistic pathways of triallate metabolism. Incubation of [14C]triallate with NADPH-fortified microsomes gave rise to metabolites generated via a number of reaction types, including sulfur oxidation/hydrolysis and hydroxylation of the allylic thiol moiety accompanied by rearrangement. Addition of glutathione (GSH) to microsomal incubations resulted in the formation of GSH conjugates arising via conjugate addition of glutathione to metabolic intermedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…This mechanism was proposed for the TZD ring opening of troglitazone by Kassahun et al (2001). A similar mechanism was also proposed by Hackett et al (1993) and Nadeau et al (1993) for the metabolism of the herbicide, triallate. Direct oxidation of M22 to give M7, although possible, was not detected when M22 was incubated with NADPH-fortified liver microsomes.…”
Section: Discussionsupporting
confidence: 62%
“…This mechanism was proposed for the TZD ring opening of troglitazone by Kassahun et al (2001). A similar mechanism was also proposed by Hackett et al (1993) and Nadeau et al (1993) for the metabolism of the herbicide, triallate. Direct oxidation of M22 to give M7, although possible, was not detected when M22 was incubated with NADPH-fortified liver microsomes.…”
Section: Discussionsupporting
confidence: 62%
“…We also describe separate feeding experiments, using radiolabeled metabolite intermediates, which allowed us to delineate the pathways of triallate metabolism in rats. The following paper (Hackett et al, 1993) presents an investigation of triallate in vitro metabolism using rat liver enzymes and provides mechanistic details for the pathways of triallate breakdown. Several other thiocarbamate animal metabolism studies have been reported (Chen et al, 1979; Debaun et al, 1978;Hubbell and Casida, 1977; Casida et al, 1975), although little information on in vivo triallate metabolism has been available (Marsden and Casida, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman (1967), de Lorenzo et al (1978), and Sandhu and Waters (1980) suggested that a metabolite carrying the trichloroallyl moeity is probably responsible for the positive results in the Ames test with S. typhimurium strains TA100 and TA1535. More recently, Hackett et al (1993) demonstrated that trichloroacrolein is formed in vitro when triallate is incubated with S9 mix (Figure 3). However, the lability of trichloroacrolein is such that it is mainly detected as a secondary metabolite (trichloroal-lyl alcohol) or as glutathione (GSH) metabolites when GSH is available.…”
Section: Mouse Micronucleus Assaymentioning
confidence: 90%
“…Metabolic pathway for triallate (Hackett et al 1993;Nadeau et al 1993). The star ( ) indicates the site of the radiolabel.…”
Section: Figurementioning
confidence: 99%